Sertraline in symptomatic chronic breathlessness: a double blind, randomised trial. Issue 1 (17th January 2019) - Currow, David C.; Ekström, Magnus; Louw, Sandra; Hill, Julie; Fazekas, Belinda; Clark, Katherine; Davidson, Patricia M.; McDonald, Christine; Sajkov, Dimitar; McCaffrey, Nikki; Doogue, Matthew; Abernethy, Amy P.; et al.
Does sertraline provide symptomatic relief for chronic breathlessness in people with advanced disease whose underlying cause(s) are optimally treated? 223 participants with chronic breathlessness (modified Medical Research Council breathlessness scale ≥2) who had optimal treatment of underlying cause(s) were randomised 1:1 to sertraline 25–100 mg (titrated upwards over 9 days) or placebo for 4 weeks. The primary outcome was the proportion who had an improvement in intensity of current breathlessness >15% from baseline on a 100-mm visual analogue scale. The proportion of people responding to sertraline was similar to placebo for current breathlessness on days 26–28 (OR 1.00, 95% CI 0.71–1.40) and for other measures of breathlessness. Quality of life in the sertraline arm had a higher likelihood of improving than in the placebo arm over the 4 weeks (OR 0.21, 95% CI 0.01–0.41; p=0.044). No differences in performance status, anxiety and depression, or survival were observed. Adverse event rates were similar between arms. Sertraline does not appear to provide any benefit over placebo in the symptomatic relief of chronic breathlessness in this patient population. Chronic breathlessness generates suffering late in life. In this setting, titrated sertraline had similar benefits and harms to placebo in an adequately powered, multi-site, double blind, randomised controlled trial at 4 weeks. http://ow.ly/iWtH30mcMYK